2005
DOI: 10.1177/000992280504400904
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Buccal Midazolam and Rectal Diazepam for the Acute Treatment of Seizures

Abstract: In this study, the authors aimed to evaluate buccal midazolam as a practical and safe alternative medication for children who suffer from seizures in the emergency setting and in home practice or anywhere. The effects and side effects of buccal midazolam and rectal diazepam were compared in the treatment of acute convulsions in 43 children, ranging in age from 2 months to 12 years who were seen at the emergency service of the children hospital. Midazolam was given on the even days of the month and diazepam was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 20 publications
1
33
0
1
Order By: Relevance
“…Respiratory depression after rectal administration of diazepam in children was reported in five class III trials, ranging from 1.2 percent to 6.4 percent (35,41,42,45,47), while two class III trials (37,40) and two class I trials in acute repetitive seizures (59,60) reported no incidence of respiratory depression with rectal diazepam use in children. No respiratory depression was reported in one study of six children treated with rectal lorazepam (35).…”
Section: Pediatric Studiesmentioning
confidence: 99%
“…Respiratory depression after rectal administration of diazepam in children was reported in five class III trials, ranging from 1.2 percent to 6.4 percent (35,41,42,45,47), while two class III trials (37,40) and two class I trials in acute repetitive seizures (59,60) reported no incidence of respiratory depression with rectal diazepam use in children. No respiratory depression was reported in one study of six children treated with rectal lorazepam (35).…”
Section: Pediatric Studiesmentioning
confidence: 99%
“…18 Buccal midazolam has been found to be as effective as rectal diazepam in control of seizures in developed countries. 19,20 Recently, in a randomized, controlled trial, buccal midazolam was as safe as and more efficacious than rectal diazepam for the treatment of seizures in children who presented to hospitals in Great Britain. 21 Potential advantages of buccal midazolam over rectal diazepam include improved efficacy, at least in developed countries, ease of administration, and safety.…”
mentioning
confidence: 99%
“…[17][18][19][20] Seizure recurrence was significantly less common in children treated with midazolam than diazepam, in the two studies reporting on it. 17,18 In all studies, respiratory depression was uncommon in either treatment group.…”
Section: Discussionmentioning
confidence: 96%